The molecular mechanism of ferroptosis and its role in COPD - Meng, Dandan; Zhu, Chengfeng; Jia, Ruixue; Li, Zongxin; Wang, Wantao; Song, Suhua (Frontiers in Medicine, 2023)
Ferroptosis, a new type of cell death, is mainly characterized by intracellular iron accumulation and lipid peroxidation. The complex regulatory network of iron metabolism, lipid metabolism, amino acid metabolism, p53-related signaling, and Nrf2-related signaling factors is involved in the entire process of ferroptosis. It has been reported that ferroptosis is involved in the pathogenesis of neurological diseases, cancer, and ischemia–reperfusion injury. Recent studies found that ferroptosis is closely related to the pathogenesis of COPD, which, to some extent, indicates that ferroptosis is a potential therapeutic target for COPD. This article mainly discusses the related mechanisms of ferroptosis, including metabolic regulation and signaling pathway regulation, with special attention to its role in the pathogenesis of COPD, aiming to provide safe and effective therapeutic targets for chronic airway inflammatory diseases.